Pengaruh Penggunaan Model Problem Based Learning (pbl) Terhadap Motivasi Belajar Dan Perilaku Prososial Siswa Pada Pembelajaran Pai Sdn 82 Kota Bengkulu - Pahlawan, Pahlawan; Adisel, Adisel; Chandra, Pasmah (UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to examine the impact of the Problem - Based Learning ( PBL ) model on students ' learning motivation and prosocial behavior in Islamic Education at SDN 82 Bengkulu City . The research is a quantitative study , using a quasi - experimental design known as